Assessment of Job Risks in the Chemical Laboratory of the Pharmacy Study Program with Job Safety Analysis (JSA) Techniques - Priska Ernestina Tenda; Faizal Reza Soeharto (poltekkes kemenkes mataram, 2021)
Chemistry laboratory organizes practicum, one of them quantitative pharmaceutical chemistry which uses a variety of chemicals and tools where if not careful, not following instructions or procedures even underestimate will cause work accidents and/ or occupational illness. Is observational descriptive research on the job risk assessments in chemical laboratories prodi pharmacy with JSA techniques aimed at finding out the risk of work performed. Population is type practicum work in chemistry laboratory and the sample is quantitative pharmaceutical chemistry practicum. Data collection techniques i.e. the work that has been selected is further determined with the working procedure and the working steps and then determines the findings of errors from each step of the work then further identify the potential hazards of each step of the work. Data analysis techniques is data from each finding of errors determined potential injury / danger / loss and its impact is then calculated risk value (risk matrix) i.e. the value of consequences multiplied by opportunity value where the results are could grouped into risk extreme, high, medium or low that continued with to determine safeguards measures that can be done to control the such danger. The results showed that performs the titration step has high very risk level value compared to another work step other of pharmaceutical chemical practicum quantitative. Titration activities carry an extreme or significant risk of harm when performed incompatible with working measures and unsafe with potential danger (disadvantage) is liquid evaporates (inhaled), disturbances The End Point of the Titration: change in color and determination of concentration, and perform movements manual repetitive continuously namely mixing the liquid or rotating the container (erlenmeyer) contains a chemical liquid by hand continuously. Chemistry laboratory organizes practicum, one of them quantitative pharmaceutical chemistry which uses a variety of chemicals and tools where if not careful, not following instructions or procedures even underestimate will cause work accidents and/ or occupational illness. Is observational descriptive research on the job risk assessments in chemical laboratories prodi pharmacy with JSA techniques aimed at finding out the risk of work performed. Population is type practicum work in chemistry laboratory and the sample is quantitative pharmaceutical chemistry practicum. Data collection techniques i.e. the work that has been selected is further determined with the working procedure and the working steps and then determines the findings of errors from each step of the work then further identify the potential hazards of each step of the work. Data analysis techniques is data from each finding of errors determined potential injury / danger / loss and its impact is then calculated risk value (risk matrix) i.e. the value of consequences multiplied by opportunity value where the results are could grouped into risk extreme, high, medium or low that continued with to determine safeguards measures that can be done to control the such danger. The results showed that performs the titration step has high very risk level value compared to another work step other of pharmaceutical chemical practicum quantitative. Titration activities carry an extreme or significant risk of harm when performed incompatible with working measures and unsafe with potential danger (disadvantage) is liquid evaporates (inhaled), disturbances The End Point of the Titration: change in color and determination of concentration, and perform movements manual repetitive continuously namely mixing the liquid or rotating the container (erlenmeyer) contains a chemical liquid by hand continuously.